Intrusion of international law into the national legal system - V. F. Anisimov; Yu. V. Truntsevskiy (Правоприменение, 2021)
The subject of the research is the peculiarities of the implementation of international law in national legal systems, the law enforcement practice of the implementation of international legal obligations of the state, doctrinal approaches to the interaction of the norms of international and domestic law. The purpose of the article is to confirm or disprove the hypothesis that the limits, forms and methods of the ex-ante intrusion of international law into the national legal system are determined not only as a result of the agreed will of States, but also against such will, under the influence of the interests of individual States or their political blocs that occupy a dominant position in an international organization. Methodology. The authors use such general theoretical and specific scientific methods as comparative analysis, generalization, interpretation and classification as well as systemic analysis and formal logical methods. The main results. The forms and methods of intrusion of international law into the legal systems are diversified. International law is not limited to interstate relations. Global processes require the development of new scientific approaches to understanding the processes of intrusion of international law into the legal systems of States. These processes require the study of the forms and methods of the impact of international law and international institutions on the national legal order. States are sometimes forced to implement measures developed in the international implementation mechanism (due to the need for international financial assistance as well as the inability to single-handedly defeat internal corruption, create a favorable international image, etc.). The international legal invasion exist already ex – post through the decisions of international judicial bodies or the assertive recommendations of international organizations. Their demands are made not just to comply with international obligations, but to change national legislation. The implementation of the norms of international law in national legal systems should be carried out at the domestic level just as much as it is necessary to fulfill these international obligations. The law enforcement practice in the state is based solely on national principles of law, and it is unacceptable to comply with the requirements from the outside to change them from the point of view of the independence of the state. It is the exclusive right of each State to determine the content of acts of interpretation of international bodies in relation to the decisions and actions of specific States from the point of view of their national interests. We prove that every state has the important right to determine the limits of the invasion of international law in their national legal system: the contents of implementing legislation; the completeness of implementation of the decisions and recommendations of international bodies and courts; the recognition of the extraterritorial validity of foreign law and forms of its implementation. Conclusions. The fundamental principle of international law- pacta sunt servanda – is transforming into a practical imperative – national legislation must change. This is due to the recognition of the jurisdiction of international judicial bodies. This is due to the extraterritorial effect of foreign law; it is connected with the transnational character of the law of international integration entities. This is due to the inability of individual States to resist exponential corruption. The continuous nature of the intrusion of international law into national legal systems is reflected in the various methods of such interference. The article proves the importance of each state having the right to independently determine the limits of the intrusion of international law into their national legal system.